Investigation on Acoustic and Thermal Properties of Powdered Granular Mask (PGM) Reinforced Green Epoxy Composites (Journal of Research Updates in Polymer Science, 2024)
This study investigates the acoustic and thermal properties of powdered granular mask (PGM) reinforced green epoxy (GE) composites, with PGM contents of 30 vol.%, 40 vol.%, and 50 vol.%. The aim is to develop sustainable, high-performance materials with enhanced insulation properties. Among the samples, S4 (PGM/50 vol.% GE) exhibited the highest Noise Reduction Coefficient (NRC) of 0.30, demonstrating excellent acoustic shielding. Increasing the GE content improved the Transmission Loss (TL) by densifying the composite structure, significantly enhancing sound attenuation. In the high-frequency range, S2 (PGM/30 vol.% GE), S3 (PGM/40 vol.% GE), and S4 recorded TL peaks of 39.3 dB, 43.5 dB, and 44.9 dB at 1372 Hz, 1552 Hz, and 1544 Hz, respectively, confirming improved acoustic performance with higher PGM content. Thermal stability also increased with higher GE content, with S4 showing the highest decomposition inflection temperature of 472°C, indicating enhanced heat resistance. The novelty of this work lies in the dual functional benefits of PGM/GE composites, which offer both superior acoustic insulation and thermal stability. These properties make the composites ideal for aircraft flooring systems, particularly in areas such as cockpits and passenger cabins, where both sound insulation and thermal control are critical. The findings underscore the potential of PGM/GE composites for sustainable, high-performance applications requiring both acoustic and thermal management.